The actual knee function was not influenced by joint line obliquity after open-wedge high tibial osteotomy - Kubota Mitsuaki; Kim Youngji; Sato Taisuke; Yamaguchi Junichiro; Ohno Ryuichi; Kaneko Kazuo; Ishijima Muneaki (SICOT-J, 2020)
Purpose: Excessive joint line obliquity (JLO) after open-wedge high tibial osteotomy (OWHTO) induces detrimental stress on the articular cartilage. The purpose of this article is to assess the correlation between JLO and the clinical results after OWHTO. Methods: 68 patients were followed up for more than 1 year. JLO was assessed using a long-leg standing anteroposterior radiograph. The knee osteoarthritis outcome score (KOOS) and KSS (Knee Society score) objective knee score were assessed as clinical scores. The Weight-bearing line ratio (WBLR), medial proximal tibial angle (MPTA), lateral distal femoral angle (LDFA), and joint line convergence angle (JLCA) were assessed as radiological parameters. The timed up-and-go (TUG) test and single-leg standing (SLS) test were performed, and the isometric muscle strength of the quadriceps and hamstrings was assessed to evaluate the knee function. The primary outcomes were the correlations between the JLO and the clinical score, radiological parameters and knee function after OWHTO. The secondary objective of this study was to detect the factor with the greatest influence on JLO. Results: There were significant correlations between the postoperative JLO and the KOOS in the subcategories of pain, activities of daily living (ADL), and sports and recreation (r = −0.311, −0.302, −0.282, p = 0.011, 0.014, 0.022, respectively). However, the postoperative JLO was not significantly correlated with the KSS, knee function, or muscle strength. The preoperative LDFA and postoperative MPTA were factors influencing increased JLO after OWHTO. Discussion: There was no significant correlation between the JLO and the actual knee function. The preoperative LDFA and postoperative MPTA were factors that influenced the increase in JLO after OWHTO.